Use multiplication to expand the expression below, then compute six squared

1 answer

To expand the expression using multiplication, let's denote the expression as \(a(b + c)\). If we assume \(a = 6\), \(b = 6\), and \(c = 0\), we can expand it as follows:

\[ 6(6 + 0) = 6 \times 6 + 6 \times 0 = 36 + 0 = 36 \]

Now, to compute six squared, we calculate:

\[ 6^2 = 6 \times 6 = 36 \]

So, the computed value of six squared is \(36\).

Similar Questions
    1. answers icon 1 answer
    1. answers icon 9 answers
    1. answers icon 7 answers
  1. h = 13.86 in16 in 16 in Compute the surface area of the chocolate tower. 443.52 in.2 443.52 in. squared 460.64 in.2 460.64 in.
    1. answers icon 3 answers
more similar questions